He looks six years younger in that Porsche: do the qualities of products transfer to their owners? - Raja Ahmad Effendi, Raja Ahmad Azmeer; Whitfield, T. W. Allan (Canadian Center of Science and Education, 2012)
Designed objects acquire and project various qualities through their appearance, materials, price, and advertising. This is clearly apparent in the automotive industry: a Ford ‘communicates’ a certain message about its product qualities, while a Porsche ‘communicates’ an entirely different message. Logic leads us to question whether designed objects – in this case cars – do in fact project a specific image or social position that is conferred upon their owners? A considerable body of literature positively answers the first question, yet the second has been neglected. The aim of the current research was to investigate if product qualities are transferred to product owners, by providing empirical evidence showing a shift in third-party perception of an owner when associated with a specific car model. Using a method derived from environmental psychology which demonstrates that the room a person inhabits affects perceptions of that person – the Room Effect – the present research sought to uncover whether the same effect could be demonstrated when associating a person with a product. An internet survey visually depicting (male/female, Asian/Caucasian) owners alongside their (Mercedes Benz/Proton) cars asked respondents to rate the owner on scales representing personality (the Five-Factor Model), physical attributes, and social attributes. Results demonstrated a Product Effect, though not as expected. The effect was most pronounced for the Caucasian male, with lesser effects for the Caucasian and Asian females, and none for the Asian male. The discussion draws on evolutionary and social psychology to provide a plausible explanation for the results.